Impact of Inadequate Food Supply on Tourism and Hospitality Industry in Angola - Manuel, Adelina (International Journal of Modern Hospitality and Tourism, 2023)
Purpose: The study sought to analyze the impact of inadequate food supply on tourism and hospitality industry in Angola Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The results show that food safety is important for the wellbeing and safety of hotel guests. Application of standard food safety systems, compliance to food safety system and implementation of food safety system impact the provision of safe food in hotels. From the study findings, it was concluded that application of standard Food safety systems, compliance to food safety system and implementation of food safety system impact the provision of safe food in hotels. Empirical findings revealed that mid- and low-tier hotels found the increases in commodity prices challenging and thus employed innovative methods to combat rising food costs. High-tier hotels were more concerned about satisfying customers' needs by maintaining high-quality food products and services. Unique Contribution to Theory, Practice and Policy: The theory of change and Maslow hierarchy of hotel expectations theory may be used to anchor future studies in the tourism sector. The study results will also benefit other stakeholders such as the policy makers as well as researchers and scholars from different parts of the world. The top management hospitality in the country will also use the study findings to improve tourism performance in all their activities and programs. The study recommends that the adoption of effective social protection development policies in tourism will help to improve efficiency in their major operations and activities.